The Importance of the Soil’s Occupation, of the Recovery and the Living Space of the Main Forest Species in the Sustainability of the Forest Areas of the Mountains of Dhaya and Mountains of Saïda (West Algeria) - Abdelkrim Kefifa; Khéloufi Benabdeli (Journal of Basic & Applied Sciences, 2013)
The study of the forests structure in the arid Mediterranean zone informs on their resilience and durability. The assessment of three parameters identified as critical in the understanding of this resilience, and these the overall occupancy rate of the soil by perennial vegetation, the recovery rate by stratum and living space of the defining species, is useful for understanding the dynamics of these plant formations. This evaluation was conducted in two bioclimatics most dominant in Algeria and throughout the Mediterranean basin and allowed to have results to classify the strata according to their importance with respect to these three criteria. It follows from the appreciation of the parameter recovery by stratum that the tree layer and shrub play a determining role in the semi-arid and sub-humid floors. In the estimation of the occupied soil it is shrub strata for the semiarid and tree layer for the sub-humid. The vital space per species depends on its density and its regenerative capacity, for the eight dominant species and main characteristics of the forests formations it ranges between 28 and 222 square meters depending on the species inducing misconduct densities and silviculturals. It is necessary to undertake work planting or silvicultural intervention to preserve these strata with the component species to be sure to provide stability to the formations under study.